Reduction of Tumor Formation in GABARAP Knockout Mice is Associated with Absence of H-ras Mutation - Firas Subhi Salah; Rolf Bräuer; Khansaa Raed Al-Saadi; Iver Petersen (Iraqi Journal of Cancer and Medical Genetics, 2022)
GABARAP gene has an essential role in the autophagic process through its involvement in the maturation of the autophagosome. The role of GABARAP in tumorigenesis is not yet clarified. It is ubiquitously expressed in all tested normal tissues, while its expression in tumors is divers. Autophagy could induce by Oncogenic Ras to handle the metabolic stress and support cell survival. In this study, we found that GABARAP knockout mice exhibited significantly less tumor formation than wild-type mice after 7,12-dimethylbenz(a)anthracene treatment. Different types of tumor developed in the mice (skin, mammary, lymphoma and liver tumors). Furthermore, the tumor occurrence started earlier in wild-type mice compared to GABARAP knockout animals, and the tumor sizes in wild-type mice were obviously larger in most of induced tumors compared to the tumors formed in GABARAP KO mice. No H-ras mutation detected in the tumors of GABARAP knockout mice compared to 5 mutations in 14 tumors of the wild-type mice which revealed by mutation analysis of tumors induced by DMBA. In conclusion, the absence of H-ras mutation in DMBA-induced tumors of GABARAP KO mice indicates the significance of GABARAP gene in tumor progression that need further studies to clarify the exact role.